Anterior Controllable Antedisplacement and Fusion (ACAF) for Cervical Stenosis Patients With Hyperextension Injury: A Retrospective Study - Shuangxi Sun; Yingying Miao; Tao Xu; Kaiqiang Sun; Yijuan Lu; Jingchuan Sun; Jiuyi Sun; Jiangang Shi (Orthopaedic Surgery)
ABSTRACT Objective Central cord syndrome (CCS) is an incomplete spinal cord injury (SCI) causing severe motor weakness, and timely decompression via surgical intervention facilitates better recovery. Anterior controllable antedisplacement and fusion (ACAF) is a novel decompression technique and achieved satisfactory outcomes in treating cervical degenerated diseases. However, the clinical effects of ACAF on CCS remains unknown. This present study aimed to investigate the clinical outcomes of ACAF for cervical stenosis patients with CCS due to hyperextension injury. Methods This is a retrospective study, and patients who underwent ACAF due to CCS in our institution from July 2021 to December 2022 were enrolled based on the inclusion and exclusion criteria. All patients underwent x‐ray, computed tomography (CT), and magnetic resonance imaging (MRI) before and after surgery. The duration of follow‐up was at least 12 months. The radiological parameters included associated pathologies, prevertebral hyperintensity (HI), intramedullary signal intensity (ISI), and Torg–Pavlov ratio (TPR). The cervical stability was also evaluated. Neurological function was assessed using the American Spinal Injury Association (ASIA) grading system and Japanese Orthopaedic Association (JOA) score. The Mann–Whitney U test was used to compare the clinical outcomes preoperatively and postoperatively. Results Finally, 13 patients (7 male and 6 female) with the minimum of 12‐month follow‐up were finally enrolled in this study, with the mean age of 56.6 ± 12.5 years (range, 39–74 years). There were eight patients suffered CCS due to fall, three due to vehicle accident, and two due to diving injuries. The average delay from injury to surgery was 2.23 days (range, 1–4 days), and the mean duration of follow‐up was 16.1 ± 3.5 months. In terms of prevertebral HI and ISI, C4–C6 were the most affected region. In addition, 76.9% (10 of 13) patients were observed to have cervical stenosis indicated by TPR. Associated pathologies were herniated nucleus pulposus (HNP) in five patients, OPLL in three cases, and HNP‐osteophyte complexes (HNP‐OC) in six patients. At the final follow‐up, 13 patients were improved to E. The mean JOA score improved to 15.4 ± 1.0, with the recovery rate of 77.0% ± 12.0%. Two patients experienced postoperative dysphagia, two patients had hoarseness, and one patient suffered postoperative hematoma. Conclusions ACAF can be a good option for treating CCS patients due to hyperextension injury with underlying cervical spondylosis and stenosis.